Desenvolvimento e caracterização eletroquímica de pilha a combustível de óxido sólido - Antonio de Padua Lima Fernandes (2016)
Nowadays there is an ever growing demand for energy. In this context, various studies are conducted, searching for new forms of efficient power generation. The solid oxide fuel cells come as strong candidates since it is a device with high electric power production capacity and a steady power source. In this device the chemical energy contained in a fuel is converted directly into electricity and heat. For this technology to be increasingly widespread, it is necessary to make investments and research in optimization and development of new materials for components operating at increasingly lower temperatures, reducing production costs and increasing the devices lifespan. It is also required to make investments related to production, transport and storage of hydrogen (or fuel used). In this work modifications were made at the cathode, anode and electrolyte of the cell in order to optimize its performance. In cathodes were assessed issues such as the influence of LSCF powder composition in the electrochemical properties of functional and collector layers. The LSCF powder with the composition La0,54Sr0,44Co0,2Fe0,8O3-[delta] showed the best performance for use in the functional layer, providing more a homogeneous microstructure and adhering to the electrolyte. Whereas the LSCF in the composition La0,6Sr0,4Co0,8Fe0,2O3-[delta] showed the best composition performance for use in the collecting layer. It was also evaluated the use of carbon black and rice starch pore formers in the collector layer of the cathode, resulting that rice starch is a more suitable pore forming for the collector layer of the cathode, since the porosity of this layer presented greatest homogeneity. In the electrolyte, it was proposed to use two layers, a (ZrO2)0,92(Y2O3)0,08 YSZ and another Gd0,2CeO0,83 GDC and performed the deposition of the electrolyte by screen printing and densification of the GDC layer from doping with 2% zinc. At the anode, two compositions were tested, NiO-YSZ cermet and the other NiO-GDC. The NiO-YSZ was used as support for the produced cell and its efficiency for ethanol reforming was evaluated. The impregnation of this anode with silver, molybdenum and niobium was also carried out and its effect on ethanol reforming process was evaluated. The second anode composition was initially tested for the search, of a new choice of material, with a greater efficiency of this material in relation to the first composition studied.